Optimasi Proses Pelayanan Informasi Teknologi Di Laboratorium Bahan Konstruksi Untuk Masyarakat Kalimantan Timur - Egy Ahmad Fahroji; Arbansyah Arbansyah (Fakultas Teknik Universitas Cenderawasih, 2023)
This journal explores the optimization of information technology service processes in construction materials laboratories, with a focus on meeting the needs of the people of East Kalimantan. Through the use of the latest methods and technology, this research aims to increase the efficiency, availability and accessibility of technological information in the laboratory. The research results show that implementing this optimization strategy can significantly improve information technology services, support progress in the construction sector, and make a positive contribution to the people of East Kalimantan. This journal details an approach using literature methods to optimize the information technology service process in construction materials laboratories, with the main aim of meeting the needs and advancing the people of East Kalimantan.